2020
DOI: 10.32598/bcn.11.covid19.2500.1
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions of Psychiatric and COVID-19 Medications

Abstract: Coronavirus disease 2019 (COVID-19) has become a pandemic with 1771514 cases identified in the world and 70029 cases in Iran until April 12, 2020. The co-prescription of psychotropics with COVID-19 medication is not uncommon. Healthcare providers should be familiar with many Potential Drug-Drug Interactions (DDIs) between COVID-19 therapeutic agents and psychotropic drugs based on cytochrome P450 metabolism. This review comprehensively summarizes the current literature on DDIs between antiretroviral drugs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 108 publications
0
37
0
5
Order By: Relevance
“…Clinically significant interactions between mirtazapine and ritonavir boosted lopinavir have not been reported. No interaction has been found between mirtazapine and Hydroxychloroquine, chloroquine, ribavirin and interferons [32].…”
Section: Norepinephrine-serotonin Modulatormentioning
confidence: 91%
See 4 more Smart Citations
“…Clinically significant interactions between mirtazapine and ritonavir boosted lopinavir have not been reported. No interaction has been found between mirtazapine and Hydroxychloroquine, chloroquine, ribavirin and interferons [32].…”
Section: Norepinephrine-serotonin Modulatormentioning
confidence: 91%
“…In a clinical trial phase 1 performed on 12 subjects administration of ritonavir and lopinavir (400 mg/100 mg two times daily) resulted in 57% reduction in bupropion AUC. In another study, the results showed that high dose (600 mg two times daily) and low dose (100 mg twice daily) of ritonavir resulted in 67% and 22% lowering in bupropion serum concentrations, respectively [32].…”
Section: E Norepinephrine-dopamine Reuptake Inhibitormentioning
confidence: 95%
See 3 more Smart Citations